STUDENTS’ MOTIVATION IN LEARNING SPEAKING USING CULTURALLY RESPONSIVE TEACHING APPROACH IN HIGHER EDUCATION (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
learning motivation, especially in the development of speaking skills in higher education. The purpose of this paper is to understand the students’ motivation in learning speaking skills in higher education using culturally responsive teaching identified as CRT. In this research the researchers used a qualitative method and used open-ended interviews to collect the data, conducting interviews with three participants, all students of an English language department. During the interviews, it was kept in mind that the focus was to gather information about the student’s experiences and perspectives on the adopted culturally responsive teaching approach. In this case, thematic analysis was used to analyze the collected data, since it helps to focus on the main themes and the repeated patterns that exist in the data collected. Three major areas were discussed as follows. The first theme is positive experiences with the culturally responsive teaching approach which indicates the positive experiences of the students as the students were made to feel valued and listened to in a learning environment, which incorporates student’s cultural realities as they learn. The second theme is appreciation of cultural diversity emphasizing that the students’ cultural background should be valued and used to increase their desire and interest in learning. The third constructed theme is the positive relationship with motivation, which depicts the clerical correlation between a culturally responsive teaching approach and students’ motivation level. Implications of the findings or discussion of the study These findings imply that culturally responsive teaching could improve students’ motivation toward learning speaking skills because of the more positive classroom environment. The findings of the research add to the existing literature on teaching practices for enhanced learning among college students, particularly arguing that there is a need to consider the cultural identities of students as important determinants of teaching practice. Subsequent studies should take up the following issues in understanding the long-term effects culturally responsive teaching yields on nearly all facets of language learning and the broader application of this pedagogical approach in various learning environments. The novelty of this research is that it emphasizes the importance of recognizing and integrating students’ cultural backgrounds as a key element in creating an inclusive and supportive learning environment.
Keywords: Culturally Responsive Teaching; Speaking Skills; Students’ Motivation; Higher Education; Thematic Analysis; Qualitative Research